Veganism, carnism and communication - Martinelli, Dario (E|C, 2020)
The present essay will focus on the communication strategies managed by carnism to convey or mask (as appropriate) the type of information against which veganism is ethically interested in pointing the finger: the promotion of meatsuch as product, necessity, display of luxury goods, food and so on. In describing such cases and in offering a theoretical framework that helps us to interpret them, it will be argued here that carnism, like any other form of anthropization, is filtered through three similar but compatible mental attitudes: anthropocentrism, speciesism and anthropocracy.